Small Left Ventricular Size Is an Independent Risk Factor for Ventricular Assist Device Thrombosis. Issue 2 (February 2019) - Chivukula, Venkat Keshav; Beckman, Jennifer A.; Prisco, Anthony R.; Lin, Shin; Dardas, Todd F.; Cheng, Richard K.; Farris, Stephen D.; Smith, Jason W.; Mokadam, Nahush A.; Mahr, Claudius; Aliseda, Alberto
Abstract : The prevalence of ventricular assist device (VAD) therapy has continued to increase due to a stagnant donor supply and growing advanced heart failure (HF) population. We hypothesize that left ventricular (LV) size strongly influences biocompatibility and risk of thrombosis. Unsteady computational fluid dynamics (CFD) was used in conjunction with patient-derived computational modeling and virtual surgery with a standard, apically implanted inflow cannula. A dual-focus approach of evaluating thrombogenicity was employed: platelet-based metrics to characterize the platelet environment and flow-based metrics to investigate hemodynamics. Left ventricular end-diastolic dimensions (LVEDds) ranging from 4.5 to 6.5 cm were studied and ranked according to relative thrombogenic potential. Over 150, 000 platelets were individually tracked in each LV model over 15 cardiac cycles. As LV size decreased, platelets experienced markedly increased shear stress histories (SHs), whereas platelet residence time (RT) in the LV increased with size. The complex interplay between increased SH and longer RT has profound implications on thrombogenicity, with a significantly higher proportion of platelets in small LVs having long RT times and being subjected to high SH, contributing to thrombus formation. Our data suggest that small LV size, rather than decreased VAD speed, is the primary pathologic mechanism responsible for the increased incidence of thrombosis observed in VAD patients with small LVs.